Macrofinance Model of the Czech Economy : Asset Allocation Perspective. (IMF Working Papers; Working Paper, 2012)
The paper developes a VAR macrofinance model of the Czech economy. It shows that yield misalignments from the yields implied by the macrofinance model partially determine subsequent yield changes over three to nine months. These yield misalignments tend to persist for a number of months. This persistence of the misalignments was explained by (a) the fact that the macro-economy influences asset markets only at lower frequencies, (b) the liquidity effect particularly during the times of capital inflows to Czech Republic, and (c) the fact that not all misalignments were greater than their historical one standard deviation.